2019
DOI: 10.24289/ijsser.558658
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mental strengths of sportsmen by different variables

Abstract: Sporcuların zihinsel dayanıklılıklarının farklı değişkenlere göre incelenmesi Investigation of mental strengths of sportsmen by different variables

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…When the literature is examined, there are studies that parallel to our research findings, mental toughness scores do not differ according to the gender of athletes. 15,16,17,18,19,20,21,22 This situation is thought to be related to the similar reactions of all athletes under similar pressure and stress, regardless of gender. It is observed that athletes sometimes do not act in a healthy way as a result of the decrease in their extroversion and the limitation of their social activities due to the pressure of the athletes in the Olympic games or similar tournaments that require long-term preparation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…When the literature is examined, there are studies that parallel to our research findings, mental toughness scores do not differ according to the gender of athletes. 15,16,17,18,19,20,21,22 This situation is thought to be related to the similar reactions of all athletes under similar pressure and stress, regardless of gender. It is observed that athletes sometimes do not act in a healthy way as a result of the decrease in their extroversion and the limitation of their social activities due to the pressure of the athletes in the Olympic games or similar tournaments that require long-term preparation.…”
Section: Discussionmentioning
confidence: 84%
“…Similar to our research findings, within the scope of a study examining the mental toughness in football players, it was reported that mental toughness did not differ according to age groups. 19 , 20,21,41,42,43 When the literature is examined, there are also studies in which mental toughness differs according to age groups. 5,6,16,22,24,25,30,31,34,45 Confidence; it is believing in abilities to achieve the goal in difficult situations that require struggle and thinking that it is better than the opponents.…”
Section: Discussionmentioning
confidence: 99%
“…In a way that contradicts these findings, Crust et al (2014) stated that mental toughness is related to education. Şahinler and Ersoy (2019), on the other hand, stated that there is a notable difference in mental toughness score according to the educational status variable. When these results, which differ from each other, are evaluated, it can be said that the relationship between educational status and mental endurance should be examined in more detail.…”
Section: Discussionmentioning
confidence: 99%